Tác động của định hướng thời gian, chi phí và lợi ích cảm nhận đến ý định sử dụng thương mại di dộng của người tiêu dùng tại Việt Nam - Nguyễn Hữu, Khôi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This study aims at filling the gap in explaining intention to use mobile commerce from the perspective of perceived cost-benefit trade-off and time orientation an individual difference variable which is usually ignored in mobile commerce context. This study adopts partial least square structural equation modeling with SmartPLS 3.2.8 on a sample of 472 consumers to test the hypothesis. The testing results demonstrate that cost-benefit perceptions have influences on intention to use mobile commerce with similar magnitude. Moreover, perceptions of cost-benefit are influenced by time orientation and this variable also directly and indirectly affects intention to use mobile commerce via cost-benefit perceptions. With those interesting results, this study has contributions in both academic and practical ways
Keywords: Perceived cost; Perceived benefit; Time orientation; Intention to use; Mobile commerce